Antecedent Factors of Self-Directed Learning in the Workplace : A Case Study in a Private Organization in Indonesia - Ida Juliana, Hutasuhut; Shahren, Ahmad Zaidi Adruce; Hasbee, Hj Usop (Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), 2019)
Self-directed learning (SDL) is becoming a prominent issue discussed in the workplace learning topic. Each of the employees needs to be aware that organizations need people who do not only believe the importance of learning but they must have initiative and capability to learn effectively. This study aims to examine the antecedent factor of the emergence of SDL in the workplace. This study using qualitative research design, particularly case study approach conducted in a prominent motorcycle-manufacturing company in Indonesia that intentionally set the organizational direction toward a learning organization. A total of thirty staff and managers were purposively selected and interviewed using a semi-structured approach. The Data gathered were analyzed using the content analysis technique. Findings indicate three factors as the antecedent to the emergence of SDL in the workplace, namely: personal factors, organizational factors, and family support. Discussion and recommendations based on research findings will be explained later.